A novel biomimetic immunoassay method based on Pt nanozyme and molecularly imprinted polymer for the detection of histamine in foods. Issue 1 (1st January 2020) - Wang, Xiaofeng; Song, Xiaoqing; Si, Lin; Xu, Longhua; Xu, Zhixiang
ABSTRACT: This study used surface imprinting polymerization to synthesize molecularly imprinted polymer on the surface of PAF-45 material (PAF-45@MIP). SEM, FT-IR, static and kinetic adsorption experiments were adopted to investigate the morphology and properties of the MIP. The results showed that the PAF-45@MIP could rapidly absorb histamine with a high adsorption capacity. Using PAF-45@MIP as a biomimetic antibody and Pt nanozyme as a marker, a novel direct competitive biomimetic immunoassay (BIA) method for rapidly detecting histamine in foods was developed. Under optimal conditions, the limit of detection and sensitivity of the BIA method were 0.128 and 8.306 mg/L, respectively. Vinegar spiked with histamine was determined using the BIA method with recoveries ranging from 81.50% to 90.38%. The BIA method was also applied to determine histamine in dried shrimp and soy sauce samples, the results correlating well with those obtained using high-performance liquid chromatography.